2011
DOI: 10.1007/s00276-011-0799-5
|View full text |Cite
|
Sign up to set email alerts
|

CT-scan imaging of iron marked chorda tympani nerve: anatomical study and educational perspectives

Abstract: The chorda tympani nerve (CTN) is the last collateral branch of the facial nerve in its third intraosseous portion just over the stylomastoid foramen. After a curved course against the medial aspect of the tympanum where it is likely to be injured in middle ear surgery, CTN reaches the lingual nerve in the infratemporal fossa. Knowledge of CTN topographic anatomy is not easily achieved by the students because of the deep location of this thin structure. The aim of this study was to assess the spatial relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 12 publications
0
11
1
Order By: Relevance
“…Tissue quality is different from in vivo tissue; however, the specimens were fresh frozen and carefully preserved to be as clinically accurate as possible. Finally, the preparation of the axillary nerve with the wire may have disrupted the anatomy; however, this is an acceptable technique, which has been used previously in neuro-anatomical investigations [15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue quality is different from in vivo tissue; however, the specimens were fresh frozen and carefully preserved to be as clinically accurate as possible. Finally, the preparation of the axillary nerve with the wire may have disrupted the anatomy; however, this is an acceptable technique, which has been used previously in neuro-anatomical investigations [15].…”
Section: Resultsmentioning
confidence: 99%
“…The wire was then advanced along the nerve. This technique of marking a nerve with wire has previously been described when marking the lingual and chorda tympani nerves [15]. The specimens were then turned to lie prone, and a posterior approach to the shoulder was performed.…”
Section: Methodsmentioning
confidence: 99%
“…Because dissections are unlikely to be performed by all the students [2], making good teaching prosections for gross anatomy laboratories and museums is very important.…”
Section: Introductionmentioning
confidence: 99%
“…After reviewing the literature [29], it was found that most studies paid attention to different points of the deep nerves of the human head without studying the whole course of the nerves. Some authors viewed parts of the deep nerves, some observed deep nerves using microscopic or CT imaging techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation